Re-examining the role of nuclear fusion in a renewables-based energy mix. (February 2021) - Nicholas, T.E.G.; Davis, T.P.; Federici, F.; Leland, J.; Patel, B.S.; Vincent, C.; Ward, S.H.
Abstract: Fusion energy is often regarded as a long-term solution to the world's energy needs. However, even after solving the critical research challenges, engineering and materials science will still impose significant constraints on the characteristics of a fusion power plant. Meanwhile, the global energy grid must transition to low-carbon sources by 2050 to prevent the worst effects of climate change. We review three factors affecting fusion's future trajectory: (1) the significant drop in the price of renewable energy, (2) the intermittency of renewable sources and implications for future energy grids, and (3) the recent proposition of intermediate-level nuclear waste as a product of fusion. Within the scenario assumed by our premises, we find that while there remains a clear motivation to develop fusion power plants, this motivation is likely weakened by the time they become available. We also conclude that most current fusion reactor designs do not take these factors into account and, to increase market penetration, fusion research should consider relaxed nuclear waste design criteria, raw material availability constraints and load-following designs with pulsed operation. Highlights: The advantages of nuclear fusion energy are reviewed versus other low-carbon sources. In a future renewables-dominated energy grid, fusion's competitors will be fission and gas with CCS. Recent materials research suggests fusion power plants will produce waste requiring geological disposal. The existing motivation for fusion power will weaken once decarbonisation is achieved. Fusion research should consider relaxed nuclear waste criteria, resource availability, and load-following designs.